Oxidative Stress in Cardiovascular Diseases - Emilie Dubois-Deruy; Victoriane Peugnet; Annie Turkieh; Florence Pinet (MDPI AG, 2020)
Reactive oxygen species (ROS) are subcellular messengers in signal transductions pathways with both beneficial and deleterious roles. ROS are generated as a by-product of mitochondrial respiration or metabolism or by specific enzymes such as superoxide dismutases, glutathione peroxidase, catalase, peroxiredoxins, and myeloperoxidases. Under physiological conditions, the low levels of ROS production are equivalent to their detoxification, playing a major role in cellular signaling and function. In pathological situations, particularly atherosclerosis or hypertension, the release of ROS exceeds endogenous antioxidant capacity, leading to cell death. At cardiovascular levels, oxidative stress is highly implicated in myocardial infarction, ischemia/reperfusion, or heart failure. Here, we will first detail the physiological role of low ROS production in the heart and the vessels. Indeed, ROS are able to regulate multiple cardiovascular functions, such as cell proliferation, migration, and death. Second, we will investigate the implication of oxidative stress in cardiovascular diseases. Then, we will focus on ROS produced by NAPDH oxidase or during endothelial or mitochondrial dysfunction. Given the importance of oxidative stress at the cardiovascular level, antioxidant therapies could be a real benefit. In the last part of this review, we will detail the new therapeutic strategies potentially involved in cardiovascular protection and currently under study.